RESPONS OF CACAO SEEDLINGS FERTILIZED WITH PAPUAN AYAMARU PHOSPHATE ROCK (PAPR) COMBINED WITH HUMIC ACID, INOCULATION OF AMF AND PHOSPHATE SOLUBILIZING BACTERIA - Suparno, A -; Yahya, S -; Sudrajat -; Setiadi, Y -; Idris, K - (Bionatura, 2012)
The effect of Papuan Ayamaru Phosphate Rock (PAPR) dosage levels combined with inoculation of humic acid (HA), arbuscular mycorrhizae fungi (AMF), and Phosphate Solubilizing Bacteria (PSB) was studied on the growth of cocoa seedling. The treatment of PAPR consisted of 0, 1, 2, 4 g P2O5 / seedling and 2 g P2O5 SP-36 /seedling as control. Ultisol was collected from Jasinga, West Java and used as planting media, while the Upper Amazone Hybrid F-1 cocoa seeds were obtained from the Coffee and Cacao Research Center, Jember-East Java. The study was carried out for 16 weeks after planting under 60 % of shading net. All fertilization treatments which were inoculated with AMF produced better seedling growth compared to the seedling growth without AMF. The response of seedling growth and P available content of the media due to 4.0 g P2O5 plant-1 of PAPR was still linearly increased. The responses were improved by application of HA, AMF and PSB inoculation. Synthesis of organic acids by PSB inoculation and the release of acid phosphatase by AMF to the media was an indication that there was an external mechanism of P solubilization of the phosphate rock. The effectiveness of AMF, HA and PSB on shoot dry weight were 104.29%, 4.38% and 4.24% respectively on P uptake were 191.00%, 33.20% and 18.31% respectively, on root colonization were 681.82%, 10.26% and 6.17% respectively, on acid phosphatase activity were 30.07%, 7.58%, 7.34% respectively, and on PAPR efficiency were 104.29%, 438% and 4.24% respectively.Key words: biofertilizer, inoculation, mycorrhizae, phosphate rock, SP-36